Matching Accounting Curricula with Market Demands: A Study on the University of Rajshahi in Bangladesh - Hossain, S. Z.; Haque, M. A.; Rahman, M. T. (Archives of Business Research, 2020)
The study strived to explore whether the accounting curricula of the University of Rajshahi fit the needs of both domestic and foreign job markets. To accomplish this purpose, we prepared five sets of Likert-type structured questionnaires and administered them to stakeholders viz faculties, students, alumni, non-academic staff, and employers. The Higher Education Quality Enhancement Program (HEQEP) of the University Grants Commission of Bangladesh provided the questionnaires. The study found a notable gap between the courses and content covered in the accounting curricula and the skills acquired by the graduates as well their skills and needs of the job market. The Department of Accounting and Information Systems of the University developed the accounting curricula without any participation of its stakeholders and professional body members. Faculties designed curricula, but it was just routine work. Recently it has mandatory to include a member from alumni, employers, and professionals in the curriculum committee. But they have very little freedom to exercise their rights and give inputs to a curriculum to meet the needs of the job market. Moreover, the prevailing lecture-based teaching-learning pedagogy and exam-based assessment practiced by universities expand the gap. The study recommends proper representation of stakeholders in the curricula Committee and designing market-led forward-looking curricula for accounting programs giving emphasis on information technology and taking into account the demands of the prevailing and prospective job markets.